Role of long noncoding RNA taurine‐upregulated gene 1 in cancers - Da, Miao; Zhuang, Jing; Zhou, Yani; Qi, Quan; Han, Shuwen (Molecular medicine (Cambridge, Mass.), 2021)
Long non-coding RNAs (lncRNAs) are a group of non-protein coding RNAs with a length of more than 200 bp. The lncRNA taurine up-regulated gene 1 ( TUG1 ) is abnormally expressed in many human malignant cancers, where it acts as a competitive endogenous RNA (ceRNA), regulating gene expression by specifically sponging its corresponding microRNAs. In the present review, we summarised the current understanding of the role of lncRNA TUG1 in cancer cell proliferation, metastasis, angiogenesis, chemotherapeutic drug resistance, radiosensitivity, cell regulation, and cell glycolysis, as well as highlighting its potential application as a clinical biomarker or therapeutic target for malignant cancer. This review provides the basis for new research directions for lncRNA TUG1 in cancer prevention, diagnosis, and treatment.